Faktor-Faktor Yang Berpengaruh Terhadap Audit Delay Pada Perusahaan Perbankan Yang Terdaftar di Bei - Cut Delsie Hasrina; Agusmadi Agusmadi; Darnisah Darnisah (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Every company have to prepare financial statements and these reports must be reported, but there are companies that report financial statements that are not on time, which causes some companies to not report audited financial statements. The purpose of this study was to examine the effect of company size, solvency, profitability, and company age on audit delayThis research is a type of quantitative research with a quantitative descriptive approach. The population in this study are banking companies listed on the Indonesia Stock Exchange in 2018-2021. The sample in this study amounted to 39 companies. The sampling method in this study used a purposive sampling method. Methods of data analysis using descriptive statistical methods, classical assumption test, multiple linear regression test and hypothesis testing. The results of this study indicate that company size has a significant effect on audit delay. Solvability has no significant effect on Audit Delay. Company Profitability has a significant effect on Audit Delay. Company Age The company has a significant effect on Audit Delay. Company Size, Solvability, Profitability, Company Age simultaneously or jointly affect Audit Delay.